2010
DOI: 10.4314/mejs.v2i1.49652
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Orange Peel Citrus Sinensis (L) As a Source of Repellent, Toxicant and Protectant against Zabrotes Subfasciatus (Coleoptera: Bruchidae)

Abstract: Continued application of synthetic insecticides arise development of resistance and pollution of the environment. Laboratory experiments were conducted to test the efficacy of products of orange (Citrus sinensis) peels in the control of the stored products beetle Zabrotes subfasciatus (L) in stored haricot beans (latin name). Different levels of the extracts and essential oil of Citrus sinensis was tested. Conventional synthetic insecticide, Pirimiphos-methyl, was used as a standard check. Toxicity potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 18 publications
3
19
0
1
Order By: Relevance
“…The abovementioned results are in agreement with those of Zewde and Jembere (2010) who evaluated the efficacy of products of orange (Citrus sinensis) peels for controlling the stored products beetle Zabrotes subfasciatus (L) in stored haricot beans. Powders from ground peels caused significant reduction in progeny emergence of Z. subfasciatus (P< 0.05).…”
Section: The Effect Of the Tested Materials On Rice Seeds Damagesupporting
confidence: 81%
“…The abovementioned results are in agreement with those of Zewde and Jembere (2010) who evaluated the efficacy of products of orange (Citrus sinensis) peels for controlling the stored products beetle Zabrotes subfasciatus (L) in stored haricot beans. Powders from ground peels caused significant reduction in progeny emergence of Z. subfasciatus (P< 0.05).…”
Section: The Effect Of the Tested Materials On Rice Seeds Damagesupporting
confidence: 81%
“…To these authors' knowledge, there are no studies about fumigant effects of essential oil of this variety (hamlin) of C. sinensis on insects. Zewde and Jembere (2010) studied the effect of C. sinensis essential oil on Zabrotes subfasciatus L. and showed that C. sinensis had contact toxicity on this insect pest.…”
Section: Discussionmentioning
confidence: 99%
“…Then the numbers of F1 progeny produced by the experimental insects were counted. Counting were stopped after 56 days from the day of introduction to avoid overlapping of generation following similar procedures of previous scientists (Gebre Selase and Getu, 2009;Zewde and Jembere, 2010).…”
Section: F1 Progeny Assessmentmentioning
confidence: 99%
“…Damaged grains were expressed as a percentage of the total number of seeds in each replicate. Percentage weight losses were calculated by count and weight method following similar procedures of previous scientists (Gebre Selase and Getu, 2009;Zewde and Jembere 2010) as:…”
Section: Damage and Weight Loss Assessmentmentioning
confidence: 99%